The cytological diagnosis and prognosis of malignization of cervical epithelium of uterus in pregnant women. - Sumenko V.V. (Морфологія, 2007)
The investigation is dedicated to the study of the pathological alterations of cervical epithelium of uterus, proliferative activity in the lesion focuses and the improvement of cytological diagnosis of the state of cervical epithelium of uterus. The correlation between the proliferative processes in abnormal epithelium of uterine cervix and some pathological factors of the pregnant women organism was studied. The criteria for prognosis of the cervical epithelial dysplasia in pregnant women were elaborated on this basis of our data. The pathological processes in cervical epithelium were revealed in 309 pregnant women in the first trimester (mean age of women was 26,17±0,83 years). The hormonal state of pregnant women was studied on the basis of colpocytological picture and the colpocytological types which indicate the unfavorable prognosis with a certain degree of validity were determined. The mathematic model for all cytological groups of pregnant women for prognosis of inflammatory processes, epithelial dysplasia and preinvasive cervical cancer was created. The simple and comprehensible prognostic scheme for diagnosis of epithelial dysplasia and preinvasive cervical cancer was developed.